Characterization of hAT DNA transposon superfamily in the genome of Neotropical fish Apareiodon sp. - de Oliveira, Fernanda Souza (2024)
DNA transposons are diverse in fish genomes and have been described to generate genomic evolutionary novelties. hAT transposable element data are scarce in Teleostei genomes, making it challenging to conduct comparative genomic studies to understand their neutrality or function. This study aimed to perform a genomic and molecular characterization of hAT copies to assess the diversity of these elements and associate changes in these sequences to genomic and karyotypic novelties in Apareiodon sp. The data revealed that hAT TEs are highly abundant in the Apareiodon sp. genome, with few possibly autonomous copies. Highly conserved sequences with likely functional transposases were observed in nine hAT elements. A great diversity of hAT subgroups was observed, especially from Ac, Charlie, Blackjack, Tip100, hAT6, and hAT5, and a similar wave of hAT genomic invasion was identified in the genome for these six groups of hAT sequences. The data also revealed a distinct number of microsatellites within degenerated hAT copies. hAT sites were demonstrated to be dispersed in the Apareiodon sp. chromosomes and not involved in W chromosome-specific region differentiation. In conclusion, the genomic analysis revealed a great diversity of hAT elements, possible autonomous copies, and differentiation of degenerated transposable elements into tandem sequences.